Post-vaccination hyperthermia in children: a current view of the old problem - A.L. Zaplatnikov; A.A. Garina; Lepiseva I.V; V.I. Svinitskaya; M.V. Leshik; A.V. Fursova (LCC «Medicine-Inform», 2023)
A.L. Zaplatnikov1, A.A. Girina2, I.V. Lepiseva3, V.I. Svintsitskaya1, M.V. Leshik1, A.V. Fursova1 1Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 2Khanty-Mansiysk State Medical Academy, Khanty-Mansiysk, Russian Federation 3Children's Republican Hospital, Petrozavodsk, Russian Federation According to the World Health Organization, "immunization is recognized as a core component of the human right to health." However, the successes of vaccine prophylaxis could be nullified by the currently common vaccine hesitancy. The reasons behind immunization refusal encompass misconceptions related to a high rate of vaccination complications and a considerable overestimation of the role of vaccine adverse events in the development of various pathological conditions. In this context, particular concerns are caused by the potential occurrence of fever in children after an immunization and the risk of febrile seizures that may develop under such circumstances. The article is focused on the prevention and treatment of hyperthermia occurring after an immunization. However, based on the analysis of research findings a conclusion has been made that the administration of antipyretic analgesics (acetaminophen, ibuprofen) before vaccination does not prevent the onset of febrile seizures. At the same time, the use of mentioned drugs during the developed post-vaccination hyperthermia is justified and characterized by a high therapeutic efficacy. As emphasized, the early administration of antipyretic analgesics to control fever after vaccination could be recommended to children with febrile seizures in the medical history. The authors present the latest data of scientific literature demonstrating that the prophylactic antipyretic administration before an immunization may affect the vaccine-induced immunity and should not be recommended for a common use. Keywords: antipyretics, acetaminophen, vaccine adverse events, vaccination, children, ibuprofen, immunization, paracetamol, post-vaccination hyperthermia, febrile seizures. For citation: Zaplatnikov A.L., Girina A.A., Lepiseva I.V. et al. Post-vaccination hyperthermia in children: a current view of the old problem. Russian Journal of Woman and Child Health. 2023;6(2):192-198 (in Russ.). DOI: 10.32364/2618-8430-2023-6-2-192-198.